2004
DOI: 10.1007/s10517-005-0063-2
|View full text |Cite
|
Sign up to set email alerts
|

Water and salt consumption and suppression of angiotensin-induced thirst in rats after carotid glomectomy

Abstract: Carotid glomectomy in rats reduced daily water consumption and increased daily consumption of NaCl solution. Sham operation did not modify water and salt consumption. Intraperitoneal injection of angiotensin-II did not stimulate drinking motivation in the majority of rats subjected to carotid glomectomy. Injection of angiotensin-II to sham-operated and intact animals induced active consumption of both fluids during one hour. These results attest to the involvement of the carotid body in the regulation of consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
3
5
0
Order By: Relevance
“…The mean daily volume (for 2 weeks) of NaCl solution drunk increased after the intervention in 5 of 7 rats; in 2 rats the mean volume of water drunk during a day surpassed that before surgery. The increase in the consumption of NaCl solution was in line with our previous data obtained under similar experimental conditions [7].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The mean daily volume (for 2 weeks) of NaCl solution drunk increased after the intervention in 5 of 7 rats; in 2 rats the mean volume of water drunk during a day surpassed that before surgery. The increase in the consumption of NaCl solution was in line with our previous data obtained under similar experimental conditions [7].…”
Section: Resultssupporting
confidence: 92%
“…Glomectomy suppressed the typical dipsogenic effect of intraperitoneal A-II similarly to previous experiments [7]. Analysis of the dynamics of water and NaCl consumption over 1 h after intraperitoneal injection of A-II showed that these parameters were lower in glomectomized rats compared to shamoperated controls throughout the observation period (Fig.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations